CYTOCHEMICAL STUDIES OF MITOCHONDRIA : I. THE SEPARATION AND IDENTIFICATION OF A MEMBRANE FRACTION FROM ISOLATED MITOCHONDRIA - Watson, Michael L. (The Rockefeller University Press, 1956)
Mitochondria isolated from rat liver and suspended in 0.44 M sucrose were disrupted by treatment with 0.3 per cent Na deoxycholate. The treated suspension was fractionated by differential centrifugation into a number of fractions and the respective pellets were examined in sections in the electron microscope. One of these fractions was found to consist of apparently membrane-bound (vesicular) elements. The difference between interfaces and membranes was discussed and the material of this fraction was found to meet stated requirements identifying it as membranous. A detailed study of the disruption process undergone by mitochondria in the presence of Na deoxycholate showed that the elements of this fraction were derived from structural elements assumed to be mitochondrial membranes. The findings thus demonstrate that mitochondria do possess membranes as defined and that these membranes can be isolated in a relatively pure form.